ChemInform Abstract: Efficient Access to 1, 4‐Benzothiazine: Palladium‐Catalyzed Double C—S Bond Formation Using Na2S2O3 as Sulfurating Reagent. Issue 40 (12th September 2013) - Qiao, Zongjun; Liu, Hui; Xiao, Xiao; Fu, Yana; Wei, Jianpeng; Li, Yuxue; Jiang, Xuefeng
Abstract A novel Pd‐catalyzed double C—S bond formation coupling reaction is developed.